(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The concept of distance education is gaining importance on the various developedunderdeveloped and developing countries, especially to meet the growing needs and aspirations of thepeople emerging because of explosion of knowledge, population explosion and explosion of needs. Thepresent world scenario is marked by advancement on the field of science, space and technology.Explosion of knowledge in every walk of life is marked. Thus, the formal system of education fails toincorporate significant changes due to its rigidity, high cost and the knowledge acquired fromschoolscolleges are outdated, obsolete and not the latest. Distance Education can go a long way in thisdirection in quenching the thirst of knowledge-explosion and meeting the growing needs andrequirements of the learners.Due to population explosion, there is a large increase in the number ofstudent. The formal system of education with its limited seats, admission and examination requirements,high cost can no longer afford opportunity to all students for pursuing education. Distance education isan effective and efficient alternative, because of its flexibility and it can afford adequate opportunity toone and all for pursuing their education. There are socially and economically backward students who arenot being able to provide the high cost of formal education and thus could not be able to receiveeducational facility. Distance education is essential to meet the great demand for democratization ofeducation from those sections of society especially neglected. People, who are geographically isolateddue to distance or lack of communication system, can get benefited out of the facilities provided bydistance education.